PENGARUH FASILITAS KERJA, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS LINGKUNGAN HIDUP, KEHUTANAN DAN PERTANAHAN PROPINSI PAPUA BARAT DAYA - Kanan, Yosep; Irwan, Andi; Likewati, Wa Ode (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of work facilities, organizational commitment, and organizational culture on the performance of civil servants at the DLHKP of Southwest Papua Province. This study uses a quantitative approach with a causal associative research type. The research sample consisted of 64 civil servants determined using the census method. Data were analyzed through descriptive analysis, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, coefficient of determination (R²) tests, and Effective Contributions (SE) and Relative Contributions. The results of the study indicate that partially work facilities have a positive but insignificant effect on civil servant performance with a calculated t value of 1.999 and a significance of 0.050, while organizational commitment has a positive and significant effect with a calculated t value of 5.414 and a significance of <0.001. Meanwhile, organizational culture has a positive but insignificant effect on civil servant performance with a calculated t value of 1.729 and a significance of 0.089. Simultaneously, the three independent variables have a significant effect on civil servant performance with a calculated F value of 22.093 and a significance of <0.001. The coefficient of determination (R²) value of 0.525 indicates that 52.5% of the variation in civil servant performance can be explained by work facilities, organizational commitment, and organizational culture, with organizational commitment as the most dominant variable. The effective contribution (SE) to the dependent variable (Y) is obtained from the variables Organizational Commitment (X₂) of 34.1%, Organizational Culture (X₃) of 9.8%. and Work Facilities (X₁) of 8.6%. The relative contribution (SR) of Organizational Commitment (X₂) is 64.9%, followed by Organizational Culture (X₃) of 18.8%, and Work Facilities (X₁) of 16.3%.